The evolution of Islamic fintech in Malaysia - Slimani, Intissar; Touil, Baha Eddine; Sari, Ahlem (International journal of economic perspectives, 2024)
This study aims to showcase Malaysia’s experience in the adoption of Islamic fintech, which has become one of the leading countries competing in the use of fintech in the Islamic financial industry as one of the most powerful ecosystems in this field. Our presentation of this experience found that Malaysia’s success was not a coincidence but a great effort and support on the part of stakeholders. In addition to developing plans and strategies to achieve the goals of Vision 2030, which is important to maintain Malaysia’s position as an Islamic fintech hub among the world’s countries. We also found that Malaysia has key elements for the success of Islamic finance technology, namely the sophisticated legal and regulatory infrastructure, as well as a diverse society that extends beyond traditional financial functions.